An overview of the effects of fuel molecular structure on the combustion and emissions characteristics of compression ignition engines. (January 2018) - Hellier, Paul; Talibi, Midhat; Eveleigh, Aaron; Ladommatos, Nicos
Future fuels for compression ignition engines will be required both to reduce the anthropogenic carbon dioxide emissions from fossil sources and to contribute to the reductions in the exhaust levels of pollutants, such as nitrogen oxides and particulate matter. Via various processes of biological, chemical and physical conversion, feedstocks such as lignocellulosic biomass and photosynthetic micro-organisms will yield a wide variety of potential fuel molecules. Furthermore, modification of the production processes may allow the targeted manufacture of fuels of specific molecular structure. This paper therefore presents an overview of the effects of fuel molecular structure on the combustion and emissions characteristics of compression ignition engines, highlighting in particular the submolecular features common to a variety of potential fuels. An increase in the straight-chain length of the alkyl moiety reduces the duration of ignition delay, and the introduction of double bonds or branching to an alkyl moiety both increase ignition delay. The movement of a double bond towards the centre of an alkyl chain, or the addition of oxygen to a molecule, can both increase and decrease the duration of ignition delay dependent on the overall fuel structure. Nitrogen oxide emissions are primarily influenced by the duration of fuel ignition delay, but in the case of hydrogen and methane pilot-ignited premixed combustion arise only at flame temperatures sufficiently high for thermal production. An increase in aromatic ring number and physical properties such as the fuel boiling point increase particulate matter emissions at constant combustion phasing.